Expounding lemonal terpenoids as corrosion inhibitors for copper using DFT based calculations - Samal, Pragnya Paramita; Singh, Chandrodai Pratap; Krishnamurty, Sailaja (Applied Surface Science, 2023)
The most important bottleneck in identifying an innovative and yet viable corrosion inhibitor for copper surfaces is discerning the chemical interactions at the interface of adsorbate and adsorbent. The present work, primarily, discerns the interface chemistry of green corrosion inhibitors, viz., lemonal terpenoids, with the copper surfaces for the first time. The interface chemistry is evaluated for distinct facets of copper, modelled by periodic surfaces to finite sized aggregates, with two stereoisomers viz., citral and neral through density functional calculations. The adsorption/ interaction properties between the surface and the corrosion inhibiting molecule are analysed through the electronic properties such as density of states, charge density difference plots and Bader charges where in distinct bonding mechanisms are identified as a function of varying facets. Apart from the adsorption properties, molecular packing properties are of paramount importance towards the design of an efficient corrosion inhibitor for a surface. Hence, we also analyse the intermolecular stacking energies between the inhibitors when packed among themselves in vacuum and when adhered on to metal surfaces. The studies bring forth an understanding that lemon terpenoids are highly potential corrosion inhibitors for copper surfaces, particularly, for Cu (110) surfaces both in neutral and protonated form.
Keywords: Copper surface; Density Functional Theory (DFT); Green corrosion inhibitors; Interface chemistry; Lemonal terpenoids; Molecular stacking